2021
DOI: 10.1111/micc.12697
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional microvascular network reconstruction from in vivo images with adaptation of the regional inhomogeneity in the signal‐to‐noise ratio

Abstract: Objective: Quantification of angiographic images with two-photon laser scanning fluorescence microscopy (2PLSM) relies on proper segmentation of the vascular images. However, the images contain inhomogeneities in the signal-to-noise ratio (SNR) arising from regional effects of light scattering and absorption. The present study developed a semiautomated quantification method for volume images of 2PLSM angiography by adjusting the binarization threshold according to local SNR along the vessel centerlines.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…The methods are based on a full visualization of blood plasma labelled with SR101, so the imaging field was limited to the upper cortical layers due to signal-to-noise ratio issues in our two-photon microscopic angiography. 9 Thus, the observed results on probability distribution and other capillary parameters could be specific to the cortical regions measured in this study. For example, the most prominent changes in blood volume occur in cortical layer IV during neural activation.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The methods are based on a full visualization of blood plasma labelled with SR101, so the imaging field was limited to the upper cortical layers due to signal-to-noise ratio issues in our two-photon microscopic angiography. 9 Thus, the observed results on probability distribution and other capillary parameters could be specific to the cortical regions measured in this study. For example, the most prominent changes in blood volume occur in cortical layer IV during neural activation.…”
Section: Discussionmentioning
confidence: 57%
“…28,29 However, substantial heterogeneity is present through capillary networks and even in single capillaries. 30 Therefore, in this study, the lumen diameter was measured along the centreline of the vessel in the 3D reconstructed images, 9 allowing us to determine the spatiotemporal heterogeneity in the diameter distributions. The observed variability in the capillary lumen structure could represent an anatomical variation of the capillaries, such as variable coverage by pericytes, 31 phenotypic variations in vascular endothelial cells, 32 and/or variable thickness of glycocalyx layers 33 or variable noises in the image.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The length and diameter of each segment were measured (Figure 1C). The diameter was measured at the minimum distance between the two sides of the vessel walls along the centerline 21 . In addition, the radius of curvature was measured for curved segments, and the interval between two straight segments (i.e., between the vessel centerlines) was measured within each capillary loop for straight segments (Figure 1C).…”
Section: Methodsmentioning
confidence: 99%
“…Capillaries (e.g., vessel less than 8 lm in diameter) constitute more than 50% of the parenchymal microvasculature and thus significant compartments determining cerebral blood flow (CBF) in the parenchyma. 19,20 Capillary flow spontaneously varies at low frequency ($0.1 Hz) and responds to the neuronal activity evoked. 21,22 Recent studies have shown that capillaries are involved in functional hyperemia in neurovascular coupling (for reviews [23][24][25] ).…”
Section: Introductionmentioning
confidence: 99%